Evaluation of cognitive function in bipolar disorder using the Brief Assessment of Cognition in Affective Disorders (BAC-A). (January 2015) - Bauer, Isabelle E.; Keefe, Richard S.E.; Sanches, Marsal; Suchting, Robert; Green, Charles E.; Soares, Jair C.
Abstract: Background: Although cognitive impairment is a core feature of bipolar disorder (BD) there is no instrument of choice for the assessment of bipolar patients. The aim of this study is to assess cognitive performance using the Brief Assessment of Cognition in Affective Disorders (BAC-A), a comprehensive test battery developed specifically for BD, and determine its suitability to estimate global functioning. Methods: The BAC-A was administered to 93 BD patients (M ± S.E: 35.18 ± 1.39 years) and 56 healthy controls (HC – M ± S.E: 36.17 ± 1.91 years). The scores of the BAC-A were combined in eight summary scores: visuomotor, immediate affective and non-affective memory, verbal fluency, delayed affective and non-affective memory, inhibition, and problem solving. Post hoc analyses were performed on subtests of the summary scores found to be significantly different between BD patients and HC. Correlational analyses explored the association between the Global Assessment of Functioning (GAF) score and cognitive functioning. Results: Compared to HC, BD patients showed a significant impairment in short-term non-affective memory and verbal fluency. Poorer performance in verbal memory and verbal fluency summary scores correlated positively with reduced GAF. Conclusions: Our results are consistent with previous reports of verbal memory and verbal fluency impairment in BD. The deficits in short-term memory and semantic fluency may indicate inefficient learning strategies and/or difficulties in retrieving information. The BAC-A could be used to estimate global functioning in BD patients. Highlights: We used the BAC-A, a BD-specific cognitive battery with strong psychometric properties. BD patients exhibited deficits in short-term memory and verbal fluency. Reduced cognitive functioning was associated with reduced global functioning. BD patients recalled affective words better than non-affective words.